2002
DOI: 10.1124/jpet.102.037531
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between α1-Adrenergic Receptor-Induced Contraction and Extracellular Signal-Regulated Kinase Activation in the Bovine Inferior Alveolar Artery

Abstract: The endogenous adrenergic agonists norepinephrine (NE) and epinephrine regulate vascular tone by stimulating ␣ 1 -adrenergic receptors (ARs) on smooth muscle cells to cause contraction. In addition, ␣ 1 -ARs also couple to growth factor pathways, through stimulation of mitogen-activated protein kinases (MAPKs). MAPKs are a family of serine-threonine kinases that include extracellular signal-regulated kinase (ERK) and a variety of other kinases that are able to activate transcription factors when stimulated. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Additionally, several studies suggest that ERK1/2 phosphorylation by norepinephrine may play a role in the regulation of contraction in intact vascular preparations [17,21,23,28,44] , whereas others suggest it may not [22,24] . In the present study, a specific inhibitor of ERK1/2 phosphorylation by MEK1/2, U0126, at 1 and 10 g/ml concentrations, caused a further decrease in the E max value of norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several studies suggest that ERK1/2 phosphorylation by norepinephrine may play a role in the regulation of contraction in intact vascular preparations [17,21,23,28,44] , whereas others suggest it may not [22,24] . In the present study, a specific inhibitor of ERK1/2 phosphorylation by MEK1/2, U0126, at 1 and 10 g/ml concentrations, caused a further decrease in the E max value of norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…Although ERK activation is generally involved in the regulation of gene expression via phosphorylation of transcription factors, protein synthesis and the activation of cytoplasmic and membrane proteins [16] , this pathway has also been shown to play an important role in vascular smooth muscle contraction under calcium-dependent and calciumindependent conditions [17][18][19][20] . It has been demonstrated that the MEK1/2-ERK1/2 pathway is involved in the vasoconstriction induced by G-protein-coupled agonists, such as norepinephrine, angiotensin II or 5-hydroxytryptamine [21][22][23][24] . Involvement of MAPKs including ERK1/2 has also been reported in the endotoxin-induced cellular responses, such as the increased activity of iNOS [25] .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to non-GPCR growth factor RTKs such as the epidermal growth factor receptor (EGFR), several GPCRs signal growth factor-like activity through one or more of these MAPK cascades. 13 Although ␣ 1 -AR stimulation has been shown to activate ERK1/2 (also denoted p42/p44 MAPK) in cultured SMCs, 4,14,15 no studies have determined which MAPK pathways are required for ␣ 1 -AR-induced growth in the intact artery.…”
mentioning
confidence: 99%
“…ERK1/2 activity was measured using a modification of the method described by Hague et al (2002). ERK1/2 activity was stopped by rapid aspiration of the incubation solution followed with addition of ice-cold lysis buffer containing 137 mM NaCl, 20 mM Tris HCl, 1 mM CaCl 2 , 1 mM MgCl 2 , 1% Nonidet P-40, 1 mM EDTA, 1 μM aprotinin, 100 μM phenylmethylsulfonyl fluoride, and 10 nM okadaic acid (Sigma-Aldrich).…”
Section: Western Blot Analysis Of Erk1/2mentioning
confidence: 99%
“…All three of the α 1 -adrenoceptor subtypes have been shown to couple to ERK1/2 activation in a variety of cell types (Zhong and Minneman, 1999;Hague et al, 2002;Jiao et al, 2002), although the physiological functions of this pathway are not well understood. Recently, Huang et al (2007) reported in cardiomyocytes that α 1 -adrenoceptors activate an anti-apoptotic, cell survival pathway by stimulation of ERK 1/2.…”
Section: Introductionmentioning
confidence: 99%